Hypoxemia associated with lumbar puncture in neonates - Sharma, Tripti; Ajmera, Mohit; Sharma, Gopikishan; Mayenger, Amrita (Indian Journal of Child Health, 2021)
Objectives: The objectives of the study were to study the effect of different stages of lumber puncture (LP) procedure on oxygen saturation (SpO2) in newborn baby. Materials and Methods: It was a 1-year, prospective observational study conducted in a tertiary care hospital. Forty neonates were included who fulfilled the inclusion criteria. SpO2 was measured during the different stages of LP in the recruited newborns and comparison was done between SpO2 changes in LP duration of <5 min and more than 5 min groups and the effect on SpO2 in preterm and term babies during LP. Results: Mean SpO2 during baseline, flexion, needle insertion, immediate repositioning, and 5 min after procedure were 94.5, 91.82, 88.92, 94.7, and 95.38, respectively. When compare to baseline, drop in SpO2 was found during flexion and needle insertion with p = 0.0025 and <0.0001, respectively. While comparing Mean SpO2 during different phases between duration of LP >5 min versus <5 min group, the saturation was less during flexion positioning with maximum fall at the time of needle insertion in LP duration >5 min. The regain of saturation during repositioning was more in LP <5 min versus duration >5 min group. Comparing between LP duration >5 min versus <5 min group, fall in SpO2 from baseline (5 min before LP procedure) was more in LP duration >5 min group during flexion and needle insertion phase. Hypoxemia is more in preterm than term neonates during flexion and during needle insertion, supine repositioning. Furthermore, hypoxia recovered after 5 min of supine repositioning more in term infants. Conclusions: Significant hypoxia was associated in newborn in flexion and needle insertion phase of lumbar puncture, especially in preterm newborns and those with prolonged duration of procedure.